Pengaruh Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Ekonomi Siswa Kelas XI IPS SMA Wiyata Dharma - Thasya Arnadia Marisi Sihite; Lasma Siagian; Mian Siahaan (Social Science Academic, 2026)
This study aims to determine the effect of the Think Pair Share (TPS) learning model on the economics learning outcomes of 11th-grade social studies students at Wiyata Dharma Senior High School. The background of this study is based on low student learning outcomes, which have not yet met the minimum passing grade (KKM), and a lack of innovation in developing learning models. Therefore, the Think Pair Share model is believed to be able to increase student participation and interactivity, both in terms of independent thinking, discussions with partners, and sharing in groups. This study used a quantitative experimental approach. The subjects were 11th-grade social studies 1 as the control class and 11th-grade social studies 2 as the experimental class, with a total of fifty-seven students. Data collection techniques included learning outcome tests (pre-tests and post-tests), observation, and documentation. Data analysis used t-tests and simple regression with SPSS. The results of this study indicate a significant difference between the learning outcomes of students using the Think Pair Share model and those using the conventional model. The average post-test score of students in the experimental class was higher than that of the control class. Based on the F-test results, the calculated F-value was 15.68 with a significance level of 0.000 < 0.05. This indicates that the regression model is significant, indicating that variable X influences variable Y. Therefore, H0 is rejected and H1 is accepted. This indicates that the regression model used is significant. The calculated F-value of 15.68 indicates that variable X has an overall influence on variable Y. Therefore, it can be concluded that the Think Pair Share learning model has a positive and significant effect on students' economics learning outcomes.